Mustache Baby - Heos, Bridget (Heos, Bridget. Mustache baby (Series), 2013)
"A picture book about baby Billy, who is born with a mustache, and his parents, who must figure our if it's a Good-Guy mustache, or a Bad-Guy mustache"--Provided by publisher.